ผลการสอนโดยอาจารย์พี่เลี้ยงต่อความสามารถในการแก้ปัญหาทางคลินิกของนักศึกษาพยาบาล วิทยาลัยพยาบาล สังกัดสถาบันพระบรมราชชนกกระทรวงสาธารณสุข - สุชีวา วิชัยกุล (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The purposes of this quasi-experimental research were to compare clinical problem solving ability of nursing students and to compare clinical problem solving ability of nursing students between experiment group and control group. Subjects consisted of 30 nursing students whom were equally assigned to experimental group and control group. Nursing students in the experimental group worked closly with staff nurse who was teaching by using preceptors 6 role on a one to one basis for a 2-month period. The instruments, used in this study, were developed by the researcher and test for content validity. The clinical problem solving ability was tested by the modified essay question and obtained internal reliability of 0.84. Data were analyzed by mean standard deviation and t-test. Major results of study were as follows: 1. The clinical problem solving ability of nursing students after the experiment were significantly higher than that before the experimental, at the .05 level. 2. After the experiment, the clinical problem solving ability of nursing students in the experiment group was significantly higher than that in the control group, at the .05 level.